Heroism and Patriotism in Wonder Woman movie - Rahman, Muhammad Faishal; Wiwoho, Gurendi (Universitas 17 Agustus 1945 Semarang, 2024)
The title of this research is “HEROISM AND PATRIOTISM IN WONDER WOMAN MOVIE”. `The purpose is to find out the heroisms and patriotisms in the film and analyze the reason of heroism and patriotism actions the main character. The data is in the form of dialogues, scenes, and utterances containing heroism and patriotism from Wonder Woman by Petty Jenkins (2017). I use theory of literature from M.H. Abrams, Austin Warren, and René Wellek to analyze the main characters from the film, heroism theory from Franco and Phillip Zimbardo (2006), patriotism theory from Archad (1999). This research uses qualitative research method for data analysis. This research consists two research questions, those are What motivated Diana Prince and Steve Trevor to carry out deeds deserving of the term’s heroic and patriotic? And how are Diana Prince and Steve Trevor's heroism and patriotism displayed? Before I analysis the heroism and patriotism, I analyze the connection between film and literature. To help the analysis, I use Gerald Mast (1982) theory about literature and film. Beside theory from Gerald Mast (1982), I also use theory from Damono (2005) about comparison literature and film. After that, I analyze the film as literature with theory of literature from Abrams and Wellek, Werren. Then, I analyze the character and characterization, with help from literary terms’s (2017) theories. Based on the data analysis, I get the results as follows. I find 7 cases of heroism actions and 3 cases of patriotism actions. Diana Prince and Steve Trevor exhibit heroism and patriotism in Wonder Woman through their courage, sacrifices, and dedication to protecting and serving others. Keywords: Literature, heroism, patriotism.